6(2/3x-7/6)=6*7/2

Simple and best practice solution for 6(2/3x-7/6)=6*7/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2/3x-7/6)=6*7/2 equation:


x in (-oo:+oo)

6*((2/3)*x-(7/6)) = (6*7)/2 // - (6*7)/2

6*((2/3)*x-(7/6))-((6*7)/2) = 0

6*((2/3)*x-7/6)-21 = 0

6*(2/3*x-7/6)-21 = 0

6*(2/3*x-7/6)-21 = 0

4*x-28 = 0

4*x-28 = 0

4*x-28 = 0 // + 28

4*x = 28 // : 4

x = 28/4

x = 7

x = 7

See similar equations:

| -2y-1=4x+3 | | b+9=24 | | 23x=173 | | 4(x+19)=3x+41 | | y=-4y+1 | | 2(-.26)+7.5=6.2-3(-.26) | | 13x+21=47 | | 3a+7b=1650 | | f(t)=2.25+0.75x | | 4+x=4x-23 | | 0.2c-0.6+.5c=5 | | 3(6+8)=24+18x | | 10m^2-6=404 | | -11.1-2.2x=2.2x/7.7-2x-x^2 | | x^3+5x^2-5x-25=0 | | 1x-2=6x+5 | | (3a+19)+2z= | | 5w+2=w+10 | | x-200=.2x | | x(x+8)(x+7)=0 | | 2r+3u=2(3r+6) | | -2(x+5)=4-(-5) | | 4x-20=3x+15 | | 3x^2+8x=8x^2-16x | | 5w-8=w+10 | | -1/5(x+3)=-13 | | 4n^2-9=-46 | | 6x-7x=-4 | | -3c-12=-5+6 | | 25+2r=5(t+2) | | X+y+4y+x=180 | | 4(-2x-3)+2x=36 |

Equations solver categories